A Highly Stable Physically Unclonable Function Using Algorithm-Based Mismatch Hardening Technique in 28-nm CMOS - Yang, Shao-Hong; Liu, Tsung-Te (IEEE transactions on circuits and systems. I, Regular papers, 2023)
Physically unclonable function (PUF) is an emerging security solution for Internet of Things (IoT) devices. However, PUF faces a critical design challenge: responses should remain the same regardless of environmental conditions. This article presents an algorithm-based mismatch hardening technique that provides an effective and efficient solution to stabilizing PUF responses, which could be applied to various PUF circuits. The proposed stabilization technique combines multiple mismatches to achieve high reliability with minimum loss of utility. Moreover, the proposed approach requires only the available digitized PUF responses, avoiding any auxiliary measurement circuit to minimize additional implementation and testing overhead. The PUF test chip implemented in 28-nm CMOS technology shows that the proposed stabilization technique achieves a highly stable performance, lowering the nominal bit error rate (BER) to 0.0016%. It also exhibits excellent reliability with a worst-case BER of 0.16% across 0.7 to 1.2 V and −50 to 125°C, proving to be a promising candidate for security primitive for IoT applications.